The Other Side of Wall Street - Harrison, Todd (Pearson Education, 2012)
Minyanville Media founder and former hedge fund honcho Todd Harrison shares amazing untold stories from Wall Street’s hidden side. From the adrenaline rush of trading at Morgan Stanley, to trench warfare with Galleon and Jim Cramer to valuable lessons about money and life, Harrison provides unforgettable tales from the most tumultuous era in financial history!